Expression of Membrane Progesterone Receptors in Eutopic and Ectopic Endometrium of Women with Endometriosis. (14th July 2020) - Vázquez-Martínez, Edgar Ricardo; Bello-Alvarez, Claudia; Hermenegildo-Molina, Ana Lorena; Solís-Paredes, Mario; Parra-Hernández, Sandra; Cruz-Orozco, Oliver; Silvestri-Tomassoni, J. Roberto; Escobar-Ponce, Luis F.; Hernández-López, Luis A.; Reyes-Mayoral, Christian; Olguín-Ortega, Andrea; Sánchez-Ramírez, Brenda; et al.
Abstract : Endometriosis is one of the most frequent gynecological diseases in reproductive age women, but its etiology is not completely understood. Endometriosis is characterized by progesterone resistance, which has been explained in part by a decrease in the expression of the intracellular progesterone receptor in the ectopic endometrium. Progesterone action is also mediated by nongenomic mechanisms via membrane progesterone receptors (mPRs) that belong to the class II members of the progesterone and adipoQ receptor (PAQR) family. The aim of the present study was to evaluate the expression at mRNA and protein levels of mPR members in the eutopic and ectopic endometrium of women with endometriosis. Total RNA and total protein were isolated from control endometrium (17 samples), eutopic endometrium (17 samples), and ectopic endometrium (9 samples). The expression of PAQR7 (mPR α ), PAQR8 (mPR β ), and PAQR6 (mPR δ ) at mRNA and protein levels was evaluated by RT-qPCR and Western blot, whereas PAQR5 (mPR γ ) gene expression was evaluated by RT-qPCR. Statistical analysis between comparable groups was performed using one-way ANOVA followed by Tukey's multiple comparisons test with a confidence interval of 95 %. The analysis of gene expression showed that PAQR7 and PAQR5 expression was lower in both eutopic and ectopic endometrium as compared to the endometrium of women without endometriosis, whereas the expression of PAQR8 and PAQR6 was only reduced in eutopic endometrium. Furthermore, mPR α and mPR β protein content was decreased in the ectopic endometrium of women with endometriosis. Our results demonstrate a decrease in the expression and protein content of mPRs in eutopic and ectopic endometrium of patients with endometriosis, which could contribute to the progesterone resistance observed in patients with this disease.